Hidden link prediction in stochastic social networks - Pandey, Babita 1976-; Khamparia, Aditya 1988- (IGI Global, 2020)
"This book examines the foremost techniques of hidden link predictions in stochastic social networks. It deals, principally, with methods and approaches that involve similarity index techniques, matrix factorization, reinforcement models, graph representations and community detections"--
Description based on title screen (IGI Global, viewed 04/16/2019)
Keywords: Computer network architectures; Online social networks / Data processing; Webometrics; Prediction theory; Intersection theory (Mathematics); Stochastic analysis